2021
DOI: 10.3389/fendo.2021.688237
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the Endometrium for Frozen Embryo Transfer: A Systematic Review

Abstract: Despite the worldwide increase in frozen embryo transfer, the search for the best protocol to prime endometrium continues. Well-designed trials comparing various frozen embryo transfer protocols in terms of live birth rates, maternal, obstetric and neonatal outcome are urgently required. Currently, low-quality evidence indicates that, natural cycle, either true natural cycle or modified natural cycle, is superior to hormone replacement treatment protocol. Regarding warmed blastocyst transfer and frozen embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 191 publications
0
40
0
2
Order By: Relevance
“…Moreover, an accumulating body of evidence showed that the pregnancy complications, such as hypertension disorder, and perinatal outcomes like large for gestational age, were significantly higher in the HRT cycles in the general population [ 24 26 ]. Thus, the current perspective prefers that the natural cycles are superior to HRT based on available low-quality evidence [ 27 ]. This evidence gives rise to whether the stimulated cycle is superior to the HRT cycle in the condition that the natural cycle does not apply to most women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an accumulating body of evidence showed that the pregnancy complications, such as hypertension disorder, and perinatal outcomes like large for gestational age, were significantly higher in the HRT cycles in the general population [ 24 26 ]. Thus, the current perspective prefers that the natural cycles are superior to HRT based on available low-quality evidence [ 27 ]. This evidence gives rise to whether the stimulated cycle is superior to the HRT cycle in the condition that the natural cycle does not apply to most women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in cryopreservation techniques have improved the survival of blastocyst stage embryos resulting in a significant rise in the frozen-thawed embryo transfers (FETs) [7][8][9]. The indications for FET are broad and need to be considered in the context of how ART is evolving.…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of ovarian hyperstimulation syndrome may be seen as a specific reason, though patient preference for timing of conception in any accepted indication is a key reason. Thus, FET is a rapidly increasing technique for deployed in ART [7][8][9]. However, failure of implantation is one of the major causes limiting its success.…”
Section: Introductionmentioning
confidence: 99%
“…The most optimal preparation protocol of the endometrium in the vitrified‐warmed embryo transfer cycle is still under discussion 53 . There was no insufficient evidence to reveal the difference in pregnancy rate as well as LB outcome between different endometrium preparation strategies in women following vitrified‐warmed embryo transfer according to the recent studies 54,55 .…”
Section: Discussionmentioning
confidence: 99%